Implementation of Cognitive Behavior Therapy (CBT) To Overcome The Friendship Relations of FM Children Victims of Bullying in Bandung City - Subardhini, Meiti; Maryami, Ami; Riyadi, Sabar (International Journal of Social Science and Community Service, 2024)
This study examines the implementation of behavior change techniques in specific behaviors that have been identified to impact the friendship relationships of children who have experienced bullying. The objective of this research is to provide a comprehensive description of the application of behavior change techniques in friendship relationships, focusing on cognitive and behavioral aspects. The research adopts a Single Subject Design approach, with the participants being children who have been victims of bullying in the city of Bandung. The measurement instruments used include baseline A1, treatment (B1), and baseline A2, which were determined based on the results of behavioral assessments. Through this process, 25 specific behaviors were identified and analyzed. The application of behavior change techniques aims to address maladaptive behaviors in children. The techniques employed include nourishment, systematic desensitization, and task center techniques. The findings of this research indicate that children who have experienced bullying demonstrate improvements in cognitive and behavioral aspects, as evidenced by the measurements taken during the baseline and intervention phases.